Pengaruh Model Pembelajaran CTL Ditinjau dari Motivasi Siswa terhadap Kemampuan Pemahaman Konsep Matematis Kelas VII - Ibnu Rizal Kurnia; Lilik Ariyanto; Sutrisno Sutrisno (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2019)
This research is motivated by the importance of the ability to understand students' mathematical concepts. Alternative learning to improve these abilities is a learning model of contextual teaching and learning. The purpose of this study was to determine the effect of contextual teaching and learning on the ability to understand mathematical concepts in terms of student motivation. The research design used in this study is Quasi Experimental Design with factorial 2 × 3. Sampling using Cluster Random Sampling technique. The population in this study were all seventh grade students in Bawang 1 State Middle School. The data in this study were obtained from the results of the posttest ability to understand mathematical concepts and student motivation questionnaires. Data processing is done by using the same two-way cell anava calculation followed by the Scheffe 'test and regression test to know the magnitude of the effect. Conclusions from the results of processing the data are 1) The ability to understand mathematical concepts in set material using the contextual teaching and learning learning model provides the ability to understand mathematical concepts that are the same as students with conventional learning models. 2) Students with high motivation have the ability to understand mathematical concepts better than students with low motivation, and students with moderate motivation have the ability to understand the same mathematical concepts as students who have low motivation. 3) There is no difference in students' ability to understand concepts between students who are given a contextual teaching and learning model and conventional on the level of student motivation. 4) Motivation of learning affects the ability to understand students' mathematical concepts in students given the model of contextual teaching and learning. Learning motivation can be used as an alternative to the affective aspect in measuring the ability to understand students' mathematical concepts, especially in set material because motivation affects the ability to understand mathematical concepts of class VII students.